1985
DOI: 10.1002/j.1460-2075.1985.tb03987.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific interaction of cellular factors with the B enhancer of polyoma virus.

Abstract: Specific interactions between proteins from mouse 3T6 cells and the enhancer sequence of polyoma virus were detected using the method of band shifting on polyacrylamide gels. Proteins eluted from 3T6 nuclei using a buffer containing 0.55 M NaCl, formed a stable complex with the B enhancer of polyoma virus. At least two different factors are involved in this interaction. The contact sites which were mapped on the DNA sequence using DNase I footprinting correspond to a GC‐rich palindrome surrounded by two sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 64 publications
8
91
0
Order By: Relevance
“…The properties of these elements are consistent with the hypothesis that differentiated cells contain positive trans-acting proteins (differentiators) that interact with the specific cis-acting sequences to stimulate the expression of the associated genes. This idea is also consistent with the observations and concepts of other workers (8)(9)(10)(11)(12).…”
supporting
confidence: 93%
“…The properties of these elements are consistent with the hypothesis that differentiated cells contain positive trans-acting proteins (differentiators) that interact with the specific cis-acting sequences to stimulate the expression of the associated genes. This idea is also consistent with the observations and concepts of other workers (8)(9)(10)(11)(12).…”
supporting
confidence: 93%
“…Isolation of nuclear proteins from adult rat brain and from 3T6 and PC12 cells was performed as described (Piette et al, 1985). Nuclear extracts from adult rat liver and kidney were purified according to Gorski et al (1986) and DNase I footprinting and gel shift assays carried out as previously reported (Cereghini et a]., 1987;Raymondjean et al, 1988).…”
Section: Dnase I Protection and Band-shift Assaysmentioning
confidence: 99%
“…Infected ceils were separated into cytoplasmic and nuclear fractions, and nuclei were extracted sequentially with buffers containing increasing concentrations of NaC1 by a modification of the method described by Piette et al (1985). Infected cell monolayers were washed with cold PBS and scraped into 1 ml PBS.…”
Section: Fractionation Of Cells Infected With Vaccinia Virus Recombinmentioning
confidence: 99%